Student Learning at the Interface of University and Industry Relating to Engineering Professionalism - Gwynne-Evans, Alison Joy (Critical Studies in Teaching and Learning, 2023)
The engineering profession is challenged with ensuring engineering students are prepared to work within industry in a professional and ethical manner. Reflection on the experience of professional practice is a key element in developing students' understanding of their professional and ethical roles. This paper builds on a theory of transformative learning based in the analysis of student assignments testing competence in one of the Engineering Council of South Africa's eleven exit level outcomes, that of Engineering Professionalism, within a fourth year capping course, at a South African university. It looks at final year students’ responses to engaging with the professional environment in terms of their ability to demonstrate competence in engineering professionalism. This results in a nuanced analysis of student learning relating to the different forms of knowledge connected to professionalism and ethics and, thus, contributes to building new knowledge about student learning in the in the under-graduate engineering curriculum.